Learning Predictive Models of Human Memory Landmarks - Horvitz, Eric; Koch, Paul; Dumais, Susan (Proceedings of the Cognitive Science Society, 2004)
We describe the construction of statistical models that provide inferences about the probability that subjects will consider events to be memory landmarks. We review methods and report results of experiments probing the classification accuracy and receiver-operator characteristics of the models.